High-performance rare-earth-free magnesium alloy as well as preparation process and application thereof
By developing a high -performance without rare earth and magnesium alloys containing elements such as BI, AL, SN, and CU, the problem of limited application of existing magnesium alloy materials in the engineering field has been solved, and the high yield strength, tensile strength and plastic extension extended extension The rate of magnesium alloy materials has the advantages of low cost and simple process.
Patent Information
- Application Number
- CN202411466371.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The application of existing magnesium alloy materials in the engineering field is limited by their low room temperature yield strength, tensile strength and plastic elongation. Rare earth-containing magnesium alloys are difficult to promote on a large scale due to their high cost and low plasticity.
Develop a high-performance rare earth-free magnesium alloy containing economical alloy elements such as Bi, Al, Sn and Cu. Through a simple preparation process, including smelting, solution treatment and extrusion deformation, the yield strength is over 320MPa and the tensile strength is 360MPa. Materials with a plastic elongation of more than 10%.
Magnesium alloys with excellent intensity and plastic matching are realized without heat treatment. The cost is low, the craftsmanship is simple, and it has a broad engineering application prospect.
Smart Images

Figure CN119351839A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to magnesium alloy technology, and in particular to a high-performance rare earth-free magnesium alloy, a preparation process and use thereof. Background Art
[0002] Weight reduction is the most effective way to achieve energy conservation and emission reduction goals in the fields of aviation, aerospace, transportation, etc. As the lightest metal structural material currently available, magnesium alloy has the advantages of high specific strength and specific stiffness, excellent damping and shock absorption performance, and good cutting processability. It is the preferred candidate material for lightweight engineering metal components.
[0003] Compared with commonly used metal materials such as aluminum and iron, the poor strength-plasticity matching of magnesium alloys is still an important factor hindering their widespread application in the engineering field. At present, the most widely used magnesium alloys are still commercial grades of magnesium alloys: such as AZ series, ZK series, etc. However, although commercial magnesium alloys have good plasticity after deformation, their room temperature yield strength is generally lower than 200MPa, and their tensile strength is generally lower than 320MPa. For example, the patent application with publication number CN 115647098A discloses an AZ31B magnesium alloy sheet with a tensile strength of 274-312MPa and a yield strength of 162-183MPa, which cannot meet the use requirements of high-performance metal structural materials. Rare earth magnesium alloy can obtain ultra-high strength by adding a large amount of rare earth elements and long-term aging. For example, the patent application with patent publication number CN115927939A discloses a magnesium alloy with high rare earth content and its preparation method. The alloy is Mg-9.28Gd-2.83Y-0.34Zr-0.43Nd (wt%), with a tensile strength of 451MPa and a yield strength of 374MPa, but the elongation is only 3.2%. In addition, the high raw material production cost (rare earth elements Gd, Y, Nd, etc. are expensive) and the extremely low plasticity make it difficult to promote and apply rare earth magnesium alloy on a large scale.
[0004] Therefore, it is necessary to develop a low-cost, rare earth-free magnesium alloy material with excellent strength-plasticity matching to meet the urgent demand for high-performance magnesium alloys for lightweight equipment components in the engineering field. This will also greatly promote the further promotion and application of low-cost rare earth-free magnesium alloys in the engineering field. Summary of the invention
[0005] The purpose of the present invention is to propose a high-performance rare-earth-free magnesium alloy to address the problems of low plasticity and high cost of current magnesium alloy materials containing rare earths. The core components of the alloy are all relatively economical alloying elements, and the processing technology is simple. It has excellent strength and plasticity matching without heat treatment after deformation. Its yield strength reaches more than 320MPa, its tensile strength reaches more than 360MPa, and its plastic elongation is more than 10%, and it has broad application prospects.
[0006] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is: a high-performance rare earth-free magnesium alloy, comprising the following components in percentage by weight: Bi: 4-7wt%, Al: 1-4wt%, Sn: 0.5-4wt%, Cu: 0.2-2wt%, and the rest being Mg and unavoidable impurities.
[0008] Furthermore, the high-performance rare-earth-free magnesium alloy comprises the following components in percentage by weight: Bi: 5-6wt%, Al: 2.5-3.5wt%, Sn: 2-3wt%, Cu: 0.5-1wt%, and the rest being Mg and unavoidable impurities.
[0009] Furthermore, the high-performance rare earth-free magnesium alloy has a yield strength of 320-350 MPa, a tensile strength of 360-380 MPa, and an elongation of 10-15%.
[0010] Another object of the present invention is to disclose a process for preparing a high-performance rare earth-free magnesium alloy, comprising the following steps:
[0011] (1) Raw material preparation: pure Mg ingot, pure Bi block, pure Al block, pure Sn block and pure Cu block are used as raw materials. After surface pretreatment, each raw material is weighed according to the mass percentage content;
[0012] (2) Melting: Melt pure Mg ingot, pure Al block, pure Cu block, pure Bi block and pure Sn block in a crucible with protective gas, let stand and keep warm for 10-15 min, stir to mix the melt evenly, scrape off the scum on the surface and sprinkle a covering agent on the surface to obtain a melt;
[0013] (3) Refining: Pass protective gas into the melt for refining and purification treatment for 1-5 min; then scrape off the surface scum, sprinkle a covering agent on the surface, heat it to 700±20℃ and keep it still for 10-20 min;
[0014] (4) Casting: After the insulation is completed, the surface scum is scraped off and the melt is cast into a preheated steel mold for air cooling to obtain a magnesium alloy ingot;
[0015] (5) Solution treatment: After removing the oxide scale on the surface of the magnesium alloy ingot, a two-stage solution treatment is performed, and finally quenching is completed in hot water to obtain a magnesium alloy after solution treatment;
[0016] (6) Extrusion deformation: The magnesium alloy after solution treatment is peeled and cut into specified sizes, kept at 200-350°C for 20-60 minutes, and then extruded at the corresponding holding temperature to obtain a rod-shaped or plate-shaped high-performance rare earth-free magnesium alloy.
[0017] Furthermore, the purity of the pure Mg ingot, pure Bi block, pure Al block, pure Sn block and pure Cu block is ≥ 99%. Before smelting, dirt on the surface of the raw materials is removed to reduce the introduction of inclusions.
[0018] Furthermore, the smelting in step (2) specifically comprises the following steps: introducing a protective gas into a crucible heated to 500±20°C, placing a pure Mg ingot preheated to 200±20°C, and then heating to 760±10°C to melt the pure Mg ingot to obtain a magnesium liquid; lowering the temperature to 720±5°C, sequentially adding a pure Al block preheated to 150±10°C, a pure Cu block, and a pure Bi block and a pure Sn block preheated to 50±10°C to the magnesium liquid, keeping the temperature for 10-15 minutes, stirring the melt at a constant speed for 2-3 minutes using a graphite rod to mix the melt evenly, scraping off the surface scum and sprinkling a covering agent on the surface to obtain a melt.
[0019] Furthermore, the protective gas flow rate in step (3) is 0.05-0.2 L / min / kg. Preferably, the refining treatment adopts argon refining method, and the purity of argon is ≥99%.
[0020] Furthermore, the covering agent in step (2) and step (3) comprises the following components in percentage by mass: MgCl2=47-53%, KCl=32-38%, CaCl2<1.5%, NaCl=8-12%, MgO<1%, H2O<0.5%, insoluble matter<1.5%.
[0021] Furthermore, in step (4), the preheating temperature of the steel mold is 220-280°C.
[0022] Furthermore, the casting method is a counter-gravity casting process, which effectively reduces defects in the ingot.
[0023] Furthermore, the alloy melting, standing and heat preservation, stirring, refining and casting in step (2), step (3) and step (4) are all carried out under a protective gas protection environment.
[0024] Furthermore, the protective gas is a CO2+SF6 mixed gas (mixing ratio 99:1) or high-purity argon (argon purity ≥ 99%).
[0025] Furthermore, the two-stage solution treatment in step (5) is a two-stage solution treatment method of first low temperature and then high temperature, comprising the following steps: the magnesium alloy ingot is first kept at a temperature of 350-420°C for 4-8h, and then kept at a temperature of 450-520°C for 12-20h.
[0026] Furthermore, the quenching method in step (5) is hot water quenching, and the quenching is completed in hot water at 80-100°C.
[0027] Furthermore, in step (6), the extrusion rate is 0.1-15 mm / s, and the extrusion ratio is 4-36.
[0028] Another object of the present invention is to disclose a use of a high-performance rare earth-free magnesium alloy in the field of structural materials for engineering lightweighting.
[0029] Furthermore, the high-performance rare earth-free magnesium alloy is particularly suitable for structural materials in aerospace, rail transportation and automobile manufacturing.
[0030] The high-performance rare-earth-free magnesium alloy of the present invention, its preparation process and use have the following advantages compared with the prior art:
[0031] 1) The high-performance rare earth-free magnesium alloy of the present invention improves melt fluidity and oxidation resistance by alloying Al and Cu elements, thereby improving the quality of ingot casting. The addition of Cu makes the low melting point Mg in the alloy system 17 Al 12 The phase transforms into a high melting point MgAlCu phase. The MgAlCu phase breaks during the extrusion process to provide nucleation sites for recrystallized grains. In addition, the dissolved Bi and Sn elements during the solid solution process will dynamically precipitate during the extrusion process to form a large number of high melting point nano Mg3Bi2 phases and Mg2Sn phases. High-density nano precipitation is the key to obtaining fine recrystallized grains. High strength is obtained by fine grain strengthening and precipitation strengthening. At the same time, fine grains and nano precipitation also make the alloy have excellent synergistic plasticity. This method can be used to develop high-performance rare earth-free magnesium alloys with both high strength and excellent plasticity. The room temperature (25°C) tensile yield strength is >320MPa, the tensile strength is >360MPa, and the plastic elongation is >10%.
[0032] 2) The high-performance rare-earth-free magnesium alloy of the present invention is composed of relatively economical Bi, Al, Sn and Cu elements, and has a low production cost.
[0033] 3) The raw materials of the high-performance rare earth-free magnesium alloy of the present invention are added in the form of pure elements, no intermediate alloy is required, and the burning loss is low, which greatly reduces the production cost.
[0034] 4) The high-performance rare earth-free magnesium alloy preparation process of the present invention only includes smelting, solid solution and extrusion deformation. No subsequent heat treatment is required after deformation. Compared with the large plastic deformation process and aging treatment after deformation required by most high-strength and high-plasticity magnesium alloys, it has the advantages of simple process and short production cycle, and is a short-process preparation process.
[0035] 5) The second phase of the high-performance rare earth-free magnesium alloy of the present invention is mainly Mg3Bi2 and Mg2Sn phases, and also includes part of MgAlCu phase, all of which are high-temperature thermally stable phases. Compared with conventional commercial alloys such as AZ91 and ZK60, they have better high-temperature mechanical properties.
[0036] In summary, all alloying elements of the high-performance rare earth-free magnesium alloy of the present invention are added in the form of pure elements, the smelting process is simple, and the high-density high-melting-point nano-precipitation phase and fine recrystallized grains are obtained by combining the two-stage solid solution process and the one-step extrusion deformation process, and a low-cost high-performance rare earth-free magnesium alloy with excellent strength and plasticity matching is prepared. The high-performance rare earth-free magnesium alloy of the present invention has low cost, simple preparation process, excellent room temperature mechanical properties and good high-temperature thermal stability, and has broad prospects for engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a metallographic microstructure photograph of the alloy of Example 1, low magnification;
[0038] Figure 2 This is a metallographic microstructure photograph of the alloy of Example 1, high magnification;
[0039] Figure 3 This is a scanning electron microscope microstructure photograph of the alloy of Example 1, low magnification;
[0040] Figure 4 This is a scanning electron microscope microstructure photograph of the alloy in Example 1, high magnification. DETAILED DESCRIPTION
[0041] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:
[0042] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0043] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.
[0044] In this specification, the numerical range expressed using "above" or "below" means a numerical range including the number.
[0045] In this specification, the word "may" includes both performing a certain process and not performing a certain process.
[0046] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0047] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0048] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0049] Example 1
[0050] This embodiment discloses a high-performance rare earth-free magnesium alloy, the general formula of which is: Mg-4.29Bi-2.65Al-3.88Sn-0.8Cu (wt%), and the preparation method thereof comprises the following steps:
[0051] (1) Raw material preparation: Pure Mg ingot, pure Bi block, pure Al block, pure Sn block and pure Cu block are used as raw materials, and the purity of the raw materials is ≥99%. After pretreatment of the raw material surface (such as removal of oxide scale, dirt, etc., the same as in the following embodiments), each raw material is weighed according to the above general formula.
[0052] (2) Melting: Clean the crucible and preheat it to 500°C. Place the magnesium ingot preheated to 200°C into the crucible, set the furnace temperature to 760°C, and heat it up at a rate of 10°C / min. After melting, obtain magnesium liquid. Then lower the temperature to a stable level of 720°C, and add pure Al blocks and pure Cu blocks preheated to 150°C, and pure Sn blocks and pure Bi blocks preheated to 50°C to the above magnesium liquid in sequence. Keep the temperature for 10 minutes, and stir the melt evenly with a graphite rod for 2 minutes.
[0053] (3) Argon gas was then introduced into the melt for refining and purification, with a gas flow rate of 0.1 L / min / kg and a refining time of 5 min. The surface scum was then scraped off, a covering agent was sprinkled on the surface, and the temperature was raised to 700°C and kept at this temperature for 20 min.
[0054] (4) The alloy ingot is prepared by counter-gravity casting using a metal mold. A mixed gas of CO2:SF6 (mixing ratio 99:1) is used for protection during the smelting and casting process.
[0055] (5) Solution treatment: The solution treatment process is 420℃ / 6h+480℃ / 18h.
[0056] (6) Machining: The alloy ingot is turned into a size suitable for extrusion deformation. Extrusion processing: The alloy is extruded into rods by an extruder. The main extrusion process parameters are: billet temperature, extrusion barrel temperature and die temperature are all kept consistent, all at 280°C, extrusion ratio 28, extrusion speed 0.5 mm / s, and the billet is preheated to the extrusion temperature before deformation and kept warm for 40 minutes. After the extrusion process is completed, it is air-cooled.
[0057] Tensile specimens were obtained from the alloy obtained in Example 1 and then subjected to room temperature mechanical property testing. The mechanical properties of the alloy obtained in this example are listed in Table 1. The tensile strength reached 385 MPa, the yield strength reached 367 MPa, and the elongation was 12.9%.
[0058] Example 2
[0059] This embodiment discloses a high-performance rare earth-free magnesium alloy, the general formula of which is: Mg-4.21Bi-2.82Al-3.06Sn-0.53Cu (wt%), and the preparation method thereof comprises the following steps:
[0060] (1) Raw material preparation: Pure Mg ingot, pure Bi block, pure Al block, pure Sn block and pure Cu block are used as raw materials, and the purity of the raw materials is ≥99%. After pretreatment of the raw material surface (such as removal of oxide scale, dirt, etc., the same as in the following embodiments), the raw materials are prepared according to the above general formula.
[0061] (2) Melting: Clean the crucible and preheat it to 500°C. Place the magnesium ingot preheated to 200°C into the crucible, set the furnace temperature to 760°C, and heat it up at a rate of 10°C / min. After melting, obtain magnesium liquid. Then lower the temperature to a stable level of 720°C, and add pure Al blocks and pure Cu blocks preheated to 150°C, and pure Sn blocks and pure Bi blocks preheated to 50°C to the above magnesium liquid in sequence. Keep the temperature for 10 minutes, and stir the melt evenly with a graphite rod for 2 minutes.
[0062] (3) Argon gas is then introduced into the melt for refining and purification, with a gas flow rate of 0.1 L / min / kg and a refining time of 5 min. The surface scum is then scraped off, a covering agent is sprinkled on the surface, and the temperature is raised to 720°C and kept at this temperature for 10 min.
[0063] (4) Finally, the alloy ingot is prepared by counter-gravity casting using a metal mold. During the smelting and casting process, a mixed gas of CO2:SF6 (mixing ratio 99:1) is required for protection.
[0064] (5) Solution treatment: The solution treatment process is 420℃ / 8h+480℃ / 16h.
[0065] (6) Machining: The alloy ingot is turned into a size suitable for extrusion deformation. Extrusion processing: The alloy is extruded into rods by an extruder. The main extrusion process parameters are: billet temperature, extrusion barrel temperature and die temperature are consistent, all of which are 300°C, extrusion ratio is 28, extrusion speed is 1mm / s, and the billet is preheated to the extrusion temperature before deformation and kept warm for 60 minutes. After the extrusion process is completed, it is air-cooled.
[0066] Tensile specimens were obtained from the alloy obtained in Example 2 and then subjected to room temperature mechanical property testing. The mechanical properties of the alloy obtained in this example are listed in Table 1. The tensile strength reached 362 MPa, the yield strength reached 324 MPa, and the elongation was 15.6%.
[0067] Example 3
[0068] This embodiment discloses a high-performance rare earth-free magnesium alloy, the general formula of which is: Mg-5.53Bi-2.89Al-2.62Sn-0.71Cu (wt%), and the preparation method thereof comprises the following steps:
[0069] 1) Raw material preparation: Pure Mg ingot, pure Bi block, pure Al block, pure Sn block and pure Cu block are used as raw materials, and the purity of the raw materials is ≥99%. After pretreatment of the raw material surface (such as removing oxide scale, dirt, etc., the same as in the following embodiments), the raw materials are prepared according to the above general formula.
[0070] 2) Melting: Clean the crucible and preheat it to 500℃, put the magnesium ingot preheated to 200℃ into the crucible, set the furnace temperature to 760℃, and the heating rate to 10℃ / min, and obtain magnesium liquid after melting. Then lower the temperature to 720℃, and add pure Al block and pure Sn block preheated to 150℃ and pure Sn block and pure Bi block preheated to 50℃ to the above magnesium liquid in turn; keep warm for 10min, and stir with a graphite rod at a constant speed for 2min to mix the melt evenly.
[0071] (3) Argon gas is then introduced into the melt for refining and purification, with a gas flow rate of 0.1 L / min / kg and a refining time of 5 min. The surface scum is then scraped off, a covering agent is sprinkled on the surface, and the temperature is raised to 720°C and kept at this temperature for 10 min.
[0072] (4) Finally, the alloy ingot is prepared by counter-gravity casting using a metal mold. During the smelting and casting process, a mixed gas of CO2:SF6 (mixing ratio 99:1) is required for protection.
[0073] (5) Solution treatment: The solution treatment process is 420℃ / 8h+480℃ / 16h.
[0074] (6) Machining: The alloy ingot is turned into a size suitable for extrusion deformation.
[0075] Extrusion processing: The alloy is extruded into rods by an extruder. The main extrusion process parameters are: billet temperature, extrusion barrel temperature and die temperature are consistent, all of which are 300°C, extrusion ratio is 25, extrusion speed is 0.2mm / s, and the billet is preheated to the extrusion temperature before deformation and kept warm for 40 minutes. After the extrusion process is completed, it is air-cooled.
[0076] Tensile specimens were obtained from the alloy obtained in Example 3 and then subjected to room temperature mechanical property testing. The mechanical properties of the alloy obtained in this example are listed in Table 1. The tensile strength reached 372 MPa, the yield strength reached 338 MPa, and the elongation was 13.4%.
[0077] Comparative Example 1
[0078] The comparative example discloses a magnesium alloy having a general formula of Mg-5.46Bi (wt%), and a preparation method thereof comprising the following steps:
[0079] 1) Raw material preparation: Pure Mg ingots and pure Bi blocks are used as raw materials. After pre-treatment of the raw material surface (such as removal of oxide scale, dirt, etc., the same as in the following embodiments), the raw materials are prepared according to the above general formula.
[0080] 2) Melting: Clean the crucible and preheat it to 500℃, put the magnesium ingot preheated to 200℃ into the crucible, set the furnace temperature to 760℃, and the heating rate to 10℃ / min, and obtain magnesium liquid after melting. Then lower the temperature to 720℃, add the pure Bi block preheated to 50℃ to the above magnesium liquid; keep it warm for 10min, and stir it with a graphite rod at a constant speed for 2min to mix the melt evenly;
[0081] (3) Argon gas is then introduced into the melt for refining and purification, with a gas flow rate of 0.1 L / min / kg and a refining time of 2 min. The surface scum is then scraped off, a covering agent is sprinkled on the surface, and the temperature is raised to 720°C and kept at this temperature for 20 min.
[0082] (4) Finally, the alloy ingot is prepared by counter-gravity casting using a metal mold. During the smelting and casting process, a mixed gas of CO2:SF6 (mixing ratio 99:1) is required for protection.
[0083] (5) Solution treatment: The solution treatment process is 420℃ / 4h+450℃ / 20h.
[0084] (6) Machining: The alloy ingot is turned into a size suitable for extrusion deformation. Extrusion processing: The alloy is extruded into rods by an extruder. The main extrusion process parameters are: billet temperature, extrusion barrel temperature and die temperature are all kept consistent, all at 280°C, extrusion ratio 25, extrusion speed 0.5 mm / s, and the billet is preheated to the extrusion temperature before deformation and kept warm for 30 minutes. After the extrusion process is completed, it is air-cooled.
[0085] Tensile specimens were obtained from the alloy obtained in Example 1 and then subjected to room temperature mechanical property testing. The mechanical properties of the alloy obtained in this comparative example are listed in Table 1, and the tensile strength is 253 MPa, the yield strength is 220 MPa, and the elongation is 7.3%.
[0086] Comparison of Examples 1, 2, and 3 with Comparative Example 1 shows that the Mg-Bi-Al-Sn-Cu alloy of the present invention has excellent synergistic plasticity while achieving ultra-high strength, and its strength and plasticity combination is far superior to that of the Mg-Bi binary alloy. Figure 1 and Figure 2 The metallographic structure picture of the Mg-4.29Bi-2.65Al-3.88Sn-0.8Cu (wt%) magnesium alloy prepared in Example 1 of this embodiment shows that the extruded alloy presents a typical bimodal grain structure, and the broken white MgAlCu phase is distributed in strips along the extrusion direction, surrounded by a large number of recrystallized grains, indicating that it has a strong particle-promoted nucleation effect. The average recrystallized grain size is about 1-2μm. Figure 3 and Figure 4 The scanning electron microscope micrograph of the Mg-4.29Bi-2.65Al-3.88Sn-0.8Cu (wt%) magnesium alloy prepared in Example 1 shows that there are high-density nano-Mg3Bi2 and Mg2Sn precipitations in the extruded alloy. Therefore, the alloy prepared in the present invention has excellent strength-ductility matching due to the combined effect of fine recrystallized grains and high-density nano-precipitations.
[0087] In summary, the new high-performance rare-earth-free magnesium alloy developed by the present invention has low cost, excellent performance, simple preparation process, and has broad application prospects.
[0088] Table 1 Room temperature tensile test results of the embodiments and comparative examples
[0089]
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-performance rare earth-free magnesium alloy, characterized in that: The invention comprises the following components in percentage by weight: Bi: 4-7wt%, Al: 1-4wt%, Sn: 0.5-4wt%, Cu: 0.2-2wt%, and the rest is Mg and inevitable impurities.
2. A process for preparing the high-performance rare earth-free magnesium alloy according to claim 1, characterized in that: The following steps are involved: (1) Raw material preparation: pure Mg ingot, pure Bi block, pure Al block, pure Sn block, and pure Cu block are used as raw materials. After surface pretreatment, each raw material is weighed according to the mass percentage content; (2) Melting: Melt pure Mg ingot, pure Al block, pure Cu block, pure Bi block and pure Sn block in a crucible with protective gas, let stand and keep warm for 10-15 min, stir to mix the melt evenly, scrape off the scum on the surface and sprinkle a covering agent on the surface to obtain a melt; (3) Refining: Pass protective gas into the melt for refining and purification treatment for 1-5 min; then scrape off the surface scum, sprinkle a covering agent on the surface, heat it to 700±20℃ and keep it still for 10-20 min; (4) Casting: After the insulation is completed, the surface scum is scraped off and the melt is cast into a preheated steel mold for air cooling to obtain a magnesium alloy ingot; (5) Solution treatment: After removing the oxide scale on the surface of the magnesium alloy ingot, a two-stage solution treatment is performed, and finally quenching is completed in hot water to obtain a magnesium alloy after solution treatment; (6) Extrusion deformation: The magnesium alloy after solution treatment is peeled and cut into specified sizes, kept at 200-350°C for 20-60 minutes, and then extruded at the corresponding holding temperature to obtain a rod-shaped or plate-shaped high-performance rare earth-free magnesium alloy.
3. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: The purity of the pure Mg ingot, pure Bi block, pure Al block, pure Sn block and pure Cu block is ≥99%.
4. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: Step (2) smelting: a protective gas is introduced into a crucible heated to 500±20°C, and a pure Mg ingot preheated to 200±20°C is placed in the crucible, and then the temperature is raised to 760±10°C to melt the pure Mg ingot to obtain a magnesium liquid; the temperature is lowered to 720±5°C, and a pure Al block, a pure Cu block preheated to 150±10°C, and a pure Bi block, and a pure Sn block preheated to 50±10°C are sequentially added to the magnesium liquid, and after keeping the temperature for 10-15 minutes, the melt is stirred to mix evenly, and the surface scum is scraped off and a covering agent is sprinkled on the surface to obtain a melt.
5. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: The protective gas flow rate in step (3) is 0.05-0.2 L / min / kg.
6. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: The covering agent in step (2) and step (3) includes the following components in percentage by mass: MgCl2=47-53%, KCl=32-38%, CaCl2<1.5%, NaCl=8-12%, MgO<1%, H2O<0.5%, insoluble matter<1.5%.
7. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: The alloy melting, standing and heat preservation, stirring, refining and casting in step (2), step (3) and step (4) are all carried out under a protective gas protection environment; The protective gas is a CO2+SF6 mixed gas or high-purity argon gas.
8. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: The two-stage solution treatment in step (5) is a two-stage solution treatment method of first low temperature and then high temperature, comprising the following steps: the magnesium alloy ingot is first kept at a temperature of 350-420° C. for 4-8 hours, and then kept at a temperature of 450-520° C. for 12-20 hours; And / or, step (5) is performed by quenching in hot water at 80-100°C.
9. The process for preparing a high-performance rare earth-free magnesium alloy according to claim 2, characterized in that: The extrusion rate in step (6) is 0.1-15 mm / s, and the extrusion ratio is 4-36.
10. Use of the high-performance rare earth-free magnesium alloy according to claim 1 in the field of structural materials for engineering lightweighting.
Citation Information
Patent Citations
Processing method of AZ31B magnesium alloy plate
CN115647098A
High-strength heat-resistant rare earth magnesium alloy and preparation method thereof
CN115927939A